Novel Stress-Inducible Antisense RNAs of Protein-Coding Loci Are Synthesized by RNA-Dependent RNA Polymerase. Issue 1 (14th July 2017) - Matsui, Akihiro; Iida, Kei; Tanaka, Maho; Yamaguchi, Katsushi; Mizuhashi, Kayoko; Kim, Jong-Myong; Takahashi, Satoshi; Kobayashi, Norio; Shigenobu, Shuji; Shinozaki, Kazuo; Seki, Motoaki
Abstract : Stress-inducible non-coding antisense RNAs generated by RNA-dependent RNA polymerases function in a novel abiotic stress response mechanism different from the known endogenous small RNA pathways. Abstract: Our previous study identified approximately 6, 000 abiotic stress-responsive noncoding transcripts existing on the antisense strand of protein-coding genes and implied that a type of antisense RNA was synthesized from a sense RNA template by RNA-dependent RNA polymerase ( RDR ). Expression analyses revealed that the expression of novel abiotic stress-induced antisense RNA on 1, 136 gene loci was reduced in the rdr1/2/6 mutants. RNase protection indicated that the RD29A antisense RNA and other RDR1/2/6-dependent antisense RNAs are involved in the formation of dsRNA. The accumulation of stress-inducible antisense RNA was decreased and increased in dcp5 and xrn4, respectively, but not changed in dcl2/3/4, nrpd1a and nrpd1b . RNA-seq analyses revealed that the majority of the RDR1/2/6-dependent antisense RNA loci did not overlap with RDR1/2/6-dependent 20–30 nt RNA loci. Additionally, rdr1/2/6 mutants decreased the degradation rate of the sense RNA and exhibited arrested root growth during the recovery stage following a drought stress, whereas dcl2/3/4 mutants did not. Collectively, these results indicate that RDRs have stress-inducible antisense RNA synthesis activity and a novel biological function that is different from the known endogenous small RNA pathways from protein-coding genes. These data reveal a novel mechanism of RNA regulation during abiotic stress response that involves complex RNA degradation pathways.